Greenland, view of Kjerulf Fjord and Hisinger Gletscher - Boyd, Louise Arner, 1887-1972 (1931)
August 1, 1931. Kjerulfs [Kjerulf] Fjord. Extreme inner end. Scoop Mountain, showing deep scoop of ice and snow over summit and very abrupt side facing north over Hisinger Glacier [Hisinger Gletscher], which is seen below it. The entire length of Left Valley shows with stream rising in small point-like lake created by streams off this glacier. See 24-F-11; 24-F-12; 24-F-13; 24-F-5 & 27-1-12. In foreground stream of Right Valley. Photo taken from raised land at S.W. corner of Main Valley at junction with Right, below cairn C.